Competition and Regulation in Vertically Related Markets. - Vickers, J (1995)
In an industry where naturally monopolistic and competitive activities are vertically related, should the natural monopolist be allowed also to operate in the deregulated competitive sector? This paper assumes that monopoly pricing behavior is regulated and, therefore, the effect of vertical integration on the task of regulation is central to the analysis. When vertical integration by the monopolist is allowed, the regulator's task is made harder as the monopolist has anticompetitive incentives to raise rivals' costs. On the other hand, integration may lead to less duplication of fixed costs. The overall welfare comparison between separation and integration is ambiguous.